Vides exemplars. Terciàries carmelitanes a El Carmelo Esmaltado de Roque Alberto Faci (1743). - GIMENO-MALDONADO, CRISTINA (Scripta, 2016)
Carmelo Esmaltado con tantas brillantes estrelles, cuantas lores terceras, fecundas de frutos de virtud y religión, cultivó y ijo en el cielo de la Santa Iglesia la venerable Orden Tercera de Nuestra Señora del Carmen, is the title of the book wrote by the aragonian carmelite Roque Alberto Faci (1684-1744) published in 1743. The issue is a treaty for the members of the Third Order of Carmel where we can ind several biographies of the carmelites woman of third order. What we pretend by analyzing their work and biography is to set the role of the woman of the third order in the world Carmel. For that, we aimed copyright considering religiosity and spirituality of the eighteenth century and the projection of the Enlightenment.